Recent Progress in the Multicomponent Synthesis of Pyran Derivatives by Sustainable Catalysts under Green Conditions - Suresh Maddila; Nagaraju Kerru; Sreekantha Babu Jonnalagadda (Molecules, 2022)
Pyrans are one of the most significant skeletons of oxygen-containing heterocyclic molecules, which exhibit a broad spectrum of medicinal applications and are constituents of diverse natural product analogues. Various biological applications of these pyran analogues contributed to the growth advances in these oxygen-containing molecules. Green one-pot methodologies for synthesising these heterocyclic molecules have received significant attention. This review focuses on the recent developments in synthesising pyran ring derivatives using reusable catalysts and emphasises the multicomponent reaction strategies using green protocols. The advantages of the catalysts in terms of yields, reaction conditions, and recyclability are discussed.